A Study of Mathematical Problem-Solving Ability and Academic Achievement on Functions through the KWDL Technique of Grade 10 Students at Phuket Wittayalai School, Phuket Province - ท่อทิพย์ ณัฐริกา; จิรวัฒนพาณิช อนุวัตร; ชัยเสนา กันตภณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were: 1) to investigate mathematical problem-solvingabilities, and 2) to examine the mathematics learning achievement on the topic of "Functions" of Grade 10 students using the KWDL technique. The target group consisted of 40 Grade 10 students at Phuket Wittayalai School during the second semester of the 2025 academic year. The research instruments included: 1) ten lesson plans based on the KWDL technique, 2) a mathematical problem-solving ability test, and 3) a mathematics learning achievement test. Data were analyzed using mean, standard deviation, and percentage. The instruments used in this study included lesson plans, a mathematical problem-solving ability test, and a learning achievement test. The content validity of all instruments was verified by three experts, with the Index of Item-Objective Congruence (IOC) scores ranging between 0.67 and 1.00. The findings of the research revealed the following. The research findings were as follows • The students’ mathematical problem-solving abilities after learning through the KWDL technique showed an average score of 33.15 (82.88%), Furthermore, 36 students (90% of the total) passed the 70% threshold, which was higher than the established criteria. • The mathematics learning achievement after using the KWDL technique showed an average score of 15.65 (S.D. = 2.58), accounting for 78.25%. This was higher than the pre-learning average score of 12.45 (S.D. = 3.10), which accounted for 62.25%. The number of students who passed the criteria increased from 19 to 32, representing an increase of 32.50%.